2017
DOI: 10.3389/fgene.2017.00159
|View full text |Cite
|
Sign up to set email alerts
|

Low Genetic Diversity and Structuring of the Arapaima (Osteoglossiformes, Arapaimidae) Population of the Araguaia-Tocantins Basin

Abstract: The arapaima, Arapaima gigas, is a fish whose populations are threatened by both overfishing and the ongoing destruction of its natural habitats. In the Amazon basin, varying levels of population structure have been found in A. gigas, although no data are available on the genetic diversity or structure of the populations found in the Araguaia-Tocantins basin, which has a topographic profile, hydrological regime, and history of fishing quite distinct from those of the Amazon. In this context, microsatellite mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
4
15
0
1
Order By: Relevance
“…The structuring observed in the Tocantins-Araguaia basin, which has only a single lineage, and the high Fst values recorded in the extremes of this basin are consistent with previous studies in this region, which indicate low levels of gene flow and structuring in the resident populations (Vitorino et al 2015(Vitorino et al , 2017. Historical population bottlenecks, followed by genetic drift may have further reinforced this structuring.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The structuring observed in the Tocantins-Araguaia basin, which has only a single lineage, and the high Fst values recorded in the extremes of this basin are consistent with previous studies in this region, which indicate low levels of gene flow and structuring in the resident populations (Vitorino et al 2015(Vitorino et al , 2017. Historical population bottlenecks, followed by genetic drift may have further reinforced this structuring.…”
Section: Discussionsupporting
confidence: 90%
“…The hypothesis that the genetic divergence between arapaimas is derived primarily from the geographic isolation of populations has been refuted progressively (Araripe et al 2013, Fazzi-Gomes et al 2017a, Vitorino et al 2017. The factors most frequently associated with this structuring are historical reductions in stocks (Araripe et al 2013, Vitorino et al 2015, the sedentary behavior of the species (Araripe et al 2013, Vitorino et al 2015, Fazzi-Gomes et al 2017a, the impact of fisheries on stocks (Hrbek et al 2005, Vitorino et al 2015, and the characteristics of each basin and its floodplain dynamics (Vitorino et al 2015, Watson et al 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found moderate to low population genetic structure across the range of the genus at various scales (Araripe et al, 2013;Watson et al, 2013). Most range-wide structure appears to be associated with distance between populations (Hrbek et al, 2005), and low genetic diversity within smaller portions of its range is sugges-10 e180031 [10] tive of overfishing (e.g., Araguaia-Tocantins basin; Vitorino et al, 2017). Heterotis niloticus is distributed throughout the Nilo-Sudanese region of Africa from Ethiopia to Senegal, the Chad basin, and Lake Turkana; it has been widely introduced in central and western Africa and is regionally extinct in the upper Egyptian Nile (Akinyi et al, 2010).…”
Section: Gymnarchidaementioning
confidence: 99%
“…Although it was considered a monotypic genus for over a century, five species of Arapaima should be recognized (Stewart, , ). In addition, unique genetic stocks of arapaima have been found in different regions (Araripe, do Rêgo, Queiroz, Sampaio, & Schneider, ; Santos, Sá Leitão, Paula‐Silva, & Almeida‐Val, ; Vitorino, Nogueira, Souza, Araripe, & Venere, ). In Guyana, two genotypes were found to occur in sympatry (Watson, Stewart, & Kretzer, ).…”
Section: Introductionmentioning
confidence: 99%